1984
DOI: 10.1002/bs.3830290102
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of the carrot and the stick in increasing dyadic outcomes during duopolistic bargaining

Abstract: Bargaining is a form of decision making which occurs between two o r more individuals of some subhuman species of animals as well as human beings in dyads, multiperson groups, organizations, societies, and supranational systems. This article deals with human dyads.Theory and research on the impact of threats on bargaining outcomes are mixed: Some studies find that the use of threats impairs outcomes relative to conditions in which no threats are made; other studies find that threats may be used for signaling a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1987
1987
2007
2007

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In contrast, consistent with findings that cooperation is inhibited by a fear of being taken advantage of (Insko et al, 1990), cooperative communication had little or no enhancing effect on the cooperative behavior of high-wary individuals. High-wary persons, who have a general fear of exploitation in interpersonal relationships, appear more apt than others to view promises of cooperation simply as manipulative ploys (cf., Stech, McClintock, & Moss, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, consistent with findings that cooperation is inhibited by a fear of being taken advantage of (Insko et al, 1990), cooperative communication had little or no enhancing effect on the cooperative behavior of high-wary individuals. High-wary persons, who have a general fear of exploitation in interpersonal relationships, appear more apt than others to view promises of cooperation simply as manipulative ploys (cf., Stech, McClintock, & Moss, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have observed that promises produce superior joint outcomes because they enhance feelings of mutual trust between parties (Baldwin, 1971a, b;Raven and Kruglanski, 1970; Schlenker et al, 1976; Tedeschi, 1970). The findings of others indicate that promises tend to be employed exploitatively to mislead or deceive others, and hence they lower joint dyadic outcomes (Kelley, 1966; Pilisuk and Skolnick, 1968;Stech et al, 1984).…”
Section: Prior Research On Threats and Promisesmentioning
confidence: 94%
“…Youngs (1986) has shown that conflict spirals, which are at least in part responsible for low joint outcomes, may result from matching behaviour in the exchange of threats, a pattern which would follow from Gouldner's (1960) norm of reciprocity. Other research suggests that threats lead to superior outcomes because they are being used to signal the threatener's willingness to reach some form of accommodation with the threatened (Borah, 1963 Smith and Anderson, 1975;Stech, McClintock and Moss, 1984).…”
Section: Prior Research On Threats and Promisesmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous research on the overall effects of promises and threats, most of which was conducted in the somewhat different context of bargaining, has produced mixed results (for reviews see McClintock et al, 1987; Stech, McClintock, & Moss, 1984; Tedeschi, 1970). Some findings suggest that threats may impair actors' outcomes by producing hostility and inspiring a spiral competitiveness (Youngs, 1986), whereas other studies show that threats may reinforce cooperative behavior under the contingency that accommodation to compromise is also signaled (Stech et al, 1984). Similarly, promises are not always effective as they either may not be trusted or may be interpreted as a weakness.…”
Section: Summary and Final Conclusionmentioning
confidence: 99%